SPECIFIC FEATURES OF TRAINING WRESTLING COACHES FOR YOUTH WITH DISABILITIES - Turdiyev To’xtaboy Mamatmurod o’g’li (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Annotation: This thesis examines the specific aspects of training coaches to work with young people with disabilities in wrestling. It analyzes the knowledge, skills, and  approaches  necessary  for  coaches,  considering  the  diverse  needs  and characteristics of athletes with disabilities. The thesis outlines the key competencies that  should  be  included  in  coach  training  programs,  such  as  adapted  training methodologies, safety assurance, inclusive communication, and psychological support. It also discusses the potential of modern information and communication technologies to train coaches and support their professional development.